Relationship between job stress and job satisfaction among teachers in private and international school in Malaysia - Heng, Joe Shen; Basri, Ramli; Asimiran, Soaib (Human Resource Management Academic Research Society, 2018)
This study seeks to examine the two key variables in the school context, job stress and job satisfaction among the teachers in private and international schools. Job stress was measured through stress sources and stress manifestations while job satisfaction was measured through intrinsic factor and extrinsic factor. The participants were 249 teachers in private and international school in Selangor area. Both levels of job satisfaction and job stress were recorded at a moderate level. Results indicated statistical differences in intrinsic factors of job satisfaction and work-related stressor as well as professional distress between private and international school’s teachers. Negative correlation was also found between the job stress and job satisfaction. Practical implications of the findings were discussed thoroughly to serve as guidance for the management as well as future research.